ChatGPT for Self-Regulated Teacher Professional Development: An Autoethnography in an EFL Teacher Development Course - Saiful, Jepri Ali (Institut Agama Islam Negeri Kudus, 2026)
Revealing a course instructor’s perspective on ChatGPT in English teacher education offers valuable insider insight into how English pre-service teachers learn about the teaching profession. However, this perspective remains underexplored. This autoethnography explores my experiences of integrating ChatGPT as a self-regulated learning partner in an EFL Teacher Development course for nineteen third-semester English Education students (September 2024–January 2025). Through critical reflections on my instructional decisions and interactions, I traced how my pedagogy evolved while students engaged in weekly ChatGPT conversations about the ELT profession. I implemented four key strategies: providing orientation on pedagogical AI use and prompting, requiring weekly ChatGPT engagement, fostering reflection through journals and video documentation, and connecting AI-based learning with classroom discussions. Despite challenges related to technology access and uneven digital literacy, I found ChatGPT to be valuable teaching partner to use in English teacher education to support English pre-service teachers to learn ELT profession.